2011
DOI: 10.1098/rsta.2011.0116
|View full text |Cite
|
Sign up to set email alerts
|

The mathematical challenges and modelling of hydroelasticity

Abstract: Hydroelasticity brings together hydrodynamics and elastic theories. It is concerned with deformations of elastic bodies responding to hydrodynamic excitations, which themselves depend on elastic deformation. This Theme Issue is intended to identify and to outline mathematical problems of modern hydroelasticity and to review recent developments in this area, including physically and mathematically elaborated models and the techniques used in their analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(36 citation statements)
references
References 43 publications
0
36
0
Order By: Relevance
“…Due to the mutual interaction between the fluid motion and the structural deformation, the hydrodynamic loads that elastic bodies are subjected during the water entry might differ from the loads acting on rigid bodies [24]. The concept is that the impact pressure is related to the movement of the impact region with respect to the water [25].…”
Section: Hydroelasticity During Slammingmentioning
confidence: 99%
“…Due to the mutual interaction between the fluid motion and the structural deformation, the hydrodynamic loads that elastic bodies are subjected during the water entry might differ from the loads acting on rigid bodies [24]. The concept is that the impact pressure is related to the movement of the impact region with respect to the water [25].…”
Section: Hydroelasticity During Slammingmentioning
confidence: 99%
“…The classic hydroelastic problem concerning the interaction between a deformable body and a moving fluid is a widely studied area in mathematics and engineering, because of its vast range of physical applications (Korobkin, Pȃrȃu & Vanden-Broeck 2011). One such application involves the modelling of an ice plate floating on top of water as a thin elastic sheet (Squire et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Early in 1929, Von Karman [1] firstly introduced a significant contribution on this subject. Following Karman's classic works on hull-water impact, a series of studies on the theoretical analysis of water entry problem have been reported (Wagner [2], Kapsenberg [3], Faltinsen [4][5] Morabito [6], Korobkin [7][8] and Abrate [9] et al). Due to the complexities of this problem (such as multi-physics interaction phenomenon, free surface tracking et al), only a few special cases of wedges entry water vertically at a constant velocity can be solved analytically.…”
mentioning
confidence: 99%